2018
DOI: 10.1155/2018/8956820
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food Quality Information Services on Food Supply Chain Pricing Decisions and Coordination Mechanisms Based on the O2O E-Commerce Mode

Abstract: This paper considers the price conflict problem between the online channel of a food processing factory and the offline channel of the food retailers in food supply chains by analyzing the pricing decisions and coordination mechanisms between the food processing factory and food retailers under the influence of a food quality information service. First, the Stackelberg game method and the Bertrand game method are used to optimize the pricing decisions with the goal of maximizing the profits of the food process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…It is interesting that over time, the positions show a growing tendency towards more emphasis on the categories of both external coordination and IQ. This is in line with the studies of Kaipia (2021), Wankmüller and Reiner (2020) and Yu and Ren (2018), which indicate that, on the one hand, the attention to (full) chain transparency is growing, while, on the other hand, this creates more challenges. In all research periods, we found the perception of an ongoing challenge related to the need for (full) transparency and traceability in the food supply chain.…”
Section: Discussionsupporting
confidence: 86%
“…It is interesting that over time, the positions show a growing tendency towards more emphasis on the categories of both external coordination and IQ. This is in line with the studies of Kaipia (2021), Wankmüller and Reiner (2020) and Yu and Ren (2018), which indicate that, on the one hand, the attention to (full) chain transparency is growing, while, on the other hand, this creates more challenges. In all research periods, we found the perception of an ongoing challenge related to the need for (full) transparency and traceability in the food supply chain.…”
Section: Discussionsupporting
confidence: 86%
“…It is interesting that over time, the data indicates that the positions show a pattern of a growing tendency towards more emphasis on the categories of both external coordination and IQ. This concurs with the studies discussed in Chapter 5, which indicate that on the one hand the attention into (full) chain transparency is growing, while on the other hand this creates more challenges (Kaipia, 2021;Pervaiz, Sushil, & Khanyapuss, 2017;Wankmüller & Reiner, 2020;Wolbers, Boersma, & Groenewegen, 2018;Yu & Ren, 2018). In Chapter 9, we elaborated and reflected in-depth on the findings of IQ.…”
Section: Information Quality (Iq) Perceived As Biggest Challengesupporting
confidence: 85%
“…However, determining food quality is more often by the amount and distribution of the main micronutrients in the food (Jomaa, Hwalla, & Zidek, 2016). Meanwhile, food quality information service is a signi􀅫icant criterion in consumer channel selection and purchasing decisions (Yu & Ren, 2018). Food storage is crucial to maintaining quality.…”
Section: Food Quality: Shelf Life and Food Ingredientsmentioning
confidence: 99%